Paciente de sexo femenino de 25 años diagnosticada con migraña que presenta insuficiencia de acomodación. - Fernández Avilés, Fernanda Yamilet (2021)
The present investigation describes the clinical case of a 25-year-old female patient who was diagnosed with migraine causing insufficient accommodation. Migraine is a pathology associated with factors such as stress, sensitivity to light, sounds, food, among others, that cause headaches in certain areas, these can be mild or strong and usually last 30 minutes, appearing two or more times. up to date. Insufficient accommodation is a visual problem caused by a decrease in accommodation, which makes it possible to change the focus from a distant object to a nearby one, being fundamental at the time of reading, when there is a problem, they cause visual fatigue, constant blinking, problems compression when reading. The importance of this case is to determine how the migraine is causing the lack of accommodation in the 25-year-old female patient by offering timely treatment. The diagnostic methodology was based on the completion of the optometry medical history through visual examinations that consist of the evaluation of visual acuity, amplitude of accommodation, accommodative flexibility, positive and negative relative accommodation, and theoretical information for greater understanding. Through the analysis of the results, it was determined that by not taking her medication rizatriptan for migraine and placing the optical correction, the symptoms expressed by the patient decreased, reaching the conclusion that the patient needs to visit her doctor to indicate another medication. that it does not cause many side effects and that you use single vision lenses for tasks in which you use near vision.